Akkermansia muciniphila and Gut Immune System: A Good Friendship That Attenuates Inflammatory Bowel Disease, Obesity, and Diabetes - Rodrigues, Vanessa Fernandes; Elias-Oliveira, Jefferson; Pereira, Ítalo Sousa; Pereira, Jéssica Assis; Barbosa, Sara Cândida; Machado, Melissa Santana Gonsalez; Carlos, Daniela (Frontiers in Immunology, 2022)
Akkermansia muciniphila is a gram-negative anaerobic mucus-layer-degrading bacterium that colonizes the intestinal mucosa of humans and rodents. Metagenomic data have shown an inverse correlation between abundance of A. muciniphila and diseases such as inflammatory bowel disease (IBD), obesity, and diabetes. Thus, in recent decades, the potential of this bacterium as an immunomodulatory probiotic for autoimmune and chronic inflammatory diseases has been explored in experimental models. Corroborating these human correlation data, it has been reported that A. muciniphila slows down the development and progression of diabetes, obesity, and IBD in mice. Consequently, clinical studies with obese and diabetic patients are being performed, and the preliminary results are very promising. Therefore, this mini review highlights the main findings regarding the beneficial roles of A. muciniphila and its action mechanisms in autoimmune and chronic inflammatory diseases.